Penggunaan Smartphone Berbasis Android Dalam Penerapan Location Based Service Pada Absensi Karyawan Dengan Metode OOAD - Wiyanto Wiyanto; Edora Edora (Faktor Exacta, 2023)
One of the most important activities in a company is the presence and absence of employees, this needs to be done for the continuity of activities within the company, the current system at PT. XYZ for attendance activities uses a finger print system, while for absenteeism it still uses a manual system, problems often occur in the finger print machine and are still conventional. The purpose of this study is to implement an automated employee attendance system using an Android-based location-based service so that it can make it easier for employees to perform attendance and absenteeism. This application system was developed using the OOAD (Object Oriented Analysis and Design) method, designed using UML (Unified Modeling Language) with tools from Android Studio and tested using blackbox testing